Advisers and their Students in the 21st Century: challenges for the graduate programs - Maria Helena da Nóbrega (Universidade Federal do Rio Grande do Sul, 2018)
This article aims to analyze how the academic mentoring is characterized, precisely the relationship between advisers and their students. Besides the participant observation, the methodology is based on the theoretical-bibliographic study of the subject. The analysis takes into account the orientation in the field of languages, to be precise: Portuguese for speakers of other languages, justified by the increasing internationalization of the Brazilian universities. The result shows lack of research, especially in Brazil. As a conclusion, the author recommends narrowing the relation among research, teaching and mentoring, adapting it to the 21st century, as well as providing specific training for the advisor.